Differences in production performance, fore-digestive tract microbiota, and expression levels of nutrient transporters of Hu sheep with different feed conversion ratio - Xiaobin Yang; Jiangbo Cheng; Dan Xu; Chong Li; Deyin Zhang; Yukun Zhang; Kai Huang; Xiaolong Li; Yuan Zhao; Liming Zhao; Quanzhong Xu; Zongwu Ma; et al. (Microbiology Spectrum)
ABSTRACT Increasing strain on feed resources has led to a gradual increase in feed input costs, making it necessary to improve feed efficiency in livestock and poultry. In this study, Hu sheep were divided into two groups (high and low feed conversion ratio [FCR]) according to the FCR. Based on 16S rDNA amplicon sequencing technology to compare rumen and small intestine microbial composition, the differences and similarities of production performance, expression level of intestinal nutrient-specific carrier, digestive enzyme activity, short-chain fatty acid (SCFA) content, muscle conventional nutrient content, and blood biochemical indexes of Hu sheep in high- and low-FCR groups were investigated, and correlation analysis was conducted. The results showed that Hu sheep in the low-FCR group had higher feed efficiency, average daily gain, and less fat deposition (P < 0.05). The difference in rumen microbial composition between the high- and low-FCR groups was significant (P < 0.05). Spearman’s correlation analysis showed that FCR was significantly associated with production performance such as body weight, fat deposition, and dressing percentage (P < 0.05). The levels of digestive enzyme activity and nutrient transporter carrier expression in the small intestine were higher in the low-FCR group than in the high-FCR group. Therefore, FCR can be one of the important targets of concern in Hu sheep production. Combining FCR and regulating the gastrointestinal environment of Hu sheep by nutritional means can greatly improve the production performance and economic benefit of Hu sheep.IMPORTANCEFeed costs account for a large portion of housed sheep. The purpose of comparing the performance and intestinal microbial composition of different FCR Hu sheep is to regulate the gastrointestinal microecology in production practice. This helps livestock producers choose low-FCR Hu sheep to maximize production costs, improve efficiency, and achieve the purpose of low-carbon production.